2018
DOI: 10.1101/353839
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of different pretreatments on flavonoids and antioxidant activity of Dryopteris erythrosora leave

Abstract: 18Flavonoids with wide bioactivity for medcine are vital secondary metabolite of plant. The factors 19 influenced on flavonoids had been reported. However, as the key processes lead to metabolite 20 alterations, the influences of the different pretreatments of samples on flavonoids and antioxidant 21 activity of ferns were with little information. Therefore, Dryopteris erythrosora leaves were chosen 22 as the materials for analyzing flavonoids alterations, which would not only provide the significant 23 basic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…Indeed, the antioxidant activity on DPPH, expressed as IC50 in μg / mL, of several species of the genus Dialium is reported in the literature, D. indum, 181.6 ± 0.4 [33,34], D. guineense, 50.23 ± 0.15 [35], D. corbisieri, 14.44 ± 0.12 and D. gossweileri, > 500 [36], D. cochinchinensis, 65.01 ± 0.12 [37]. This interesting antioxidant activity observed in D. angolense would be linked to the presence of phenolic compounds mainly flavonoids, identified and quantified within the plant during this study (table 2), as well as several previous studies which testify to the antioxidant activity of flavonoids [38][39][40][41][42]. Besides flavonoids, other antimalarial [43,44] and antioxidant [45][46][47] compounds belonging from other phytochemical groups identified in the leaves of D. angolense during this study has been isolate.…”
Section: Discussionsupporting
confidence: 75%
“…Indeed, the antioxidant activity on DPPH, expressed as IC50 in μg / mL, of several species of the genus Dialium is reported in the literature, D. indum, 181.6 ± 0.4 [33,34], D. guineense, 50.23 ± 0.15 [35], D. corbisieri, 14.44 ± 0.12 and D. gossweileri, > 500 [36], D. cochinchinensis, 65.01 ± 0.12 [37]. This interesting antioxidant activity observed in D. angolense would be linked to the presence of phenolic compounds mainly flavonoids, identified and quantified within the plant during this study (table 2), as well as several previous studies which testify to the antioxidant activity of flavonoids [38][39][40][41][42]. Besides flavonoids, other antimalarial [43,44] and antioxidant [45][46][47] compounds belonging from other phytochemical groups identified in the leaves of D. angolense during this study has been isolate.…”
Section: Discussionsupporting
confidence: 75%
“…Zhang et al . (2019) reported that MY3G increased and QU3R decreased during drying pre‐treatment at 75℃ in Dryopteris erythrosora leaves, whereas QU3R has better heat stability than QU3G (Rohn et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%